Análise institucional “no papel” do movimento Renovação Carismática Católica - Benelli, Sílvio José (Revista eclesiástica brasileira, 2017)
This research proposes an Institutional Analysis (IA) “on paper” of the Catholic Charismatic Renovation (CCR) movement, which emerged in the Catholic Church in 1967 and has greatly expanded, marking strong presence in Brazil, and particularly in the State of São Paulo. In this paper, we present the possibility of a paradigmatic reading that allows to contextualize the CCR movement in the ecclesiastical scenario. This type of analysis was performed only from literature review and documentational analysis, operating from a conceptual grid of IA and academic studies in the field of social psychology dealing with religious phenomena. We can consider that the CCR, as well as its mode of institutional operation, is aligned with the Roman Paradigm, which is hegemonic in the Catholic ecclesiastical context.